Pelatihan Media Pembelajaran Menggunakan Microsoft Power Point - Muhammad Fauzi, Yudi (Jurnal Pusat Studi Pendidikan Rakyat, 2022)
In an effort to improve the learning process so that it is effective and functional, the function of learning media is very important to be utilized. The use of media in the learning process is intended to enhance students' digestibility of the information or learning materials provided. Microsoft Power Point is a multimedia-based program that is specifically designed to deliver presentations that can make it an attractive communication medium. During this pandemic, many students were not familiar with Microsoft Power Point as a software capable of completing work in the animation field. Students also do not know for sure how to take advantage of this so as to be able to provide a high error rate when done individually. To find alternative solutions to the problems above, an introduction to Microsoft Power Point training was held and its benefits in the field of education. With the aim of training class X students to be able to use Microsoft Power Point and apply it in the field of Education. From the evaluation results, the results and benefits of this service activity include improving students' skills in using Microsoft Power Point to complete work in the field of Education.